The impact of granulocyte-macrophage colony-stimulating factor on lung epithelial cell injury and repair in severe influenza virus pneumonia - Schäfer, Theresa M.; Justus Liebig University Giessen (My University, 2025)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) exerts protective effects on bronchioalveolar stem cells (BASC) and alveolar epithelial cells type II (AECII) following viral lung injury by downregulating AMP-activated protein kinase (AMPK) signaling, which activates mechanistic target of rapamycin complex 1 (mTORC1). This activation supports the proliferation of epithelial stem cells and aids in the restoration of alveolar barrier function.
Keywords: lung research; infectiology; acute lung injury; ddc:500; ddc:570; ddc:610